The Green Virtues of Chinese Protectionism: A Comparative Analysis of EU and US Responses to the China Garbage Shock - Wellhausen, Rachel L.; Velut, Jean-Baptiste (Revue Interventions économiques / Papers in Political Economy, 2026)
Can economic protectionism in the Global South induce environmental reforms in the Global North? In 2017, China enacted “Operation National Sword,” which banned the import of a subset of internationally traded waste and scrap products. This unexpected and unprecedented collapse in Chinese demand – justified in China on environmental grounds and also an initial move in the brewing US-China trade war – shook global markets. Both the European Union and United States have long relied on exports to achieve “not in my backyard” (NIMBY) waste management goals, and China had become the dominant importer of a variety of their post-industrial and post-consumer products such as waste plastics. Thus, after 2017 EU and US waste exporters had to adjust, by reducing exports and/or diverting to new foreign markets. Conceivably, the collapse in global demand for certain waste products could ripple back to EU and US waste management policy, providing a sufficient shock to advance reform. At the same time, it is well established that the EU has environmental bona fides far exceeding those of the US. We use novel quantitative data to trace the nature of the shock to exports, providing evidence that disruptions to exports manifested in ways more visible to EU audiences than those in the US. Qualitatively, we show that EU-level policy has made meaningful strides, both within the EU and internationally, whereas initially bipartisan US interest frayed, leaving the problem of adjustment to US municipalities. Our analysis departs from conventional policy debates on the links between free trade and the environment to show that protective measures – not just trade agreements – can foster new policy linkages under certain circumstances. As what we term the “China garbage shock” reinforced rather than challenge the preexisting environmental policy cleavage between the EU and US, Chinese protectionism bolstered trade-environment linkages in a most-likely case but did not overcome trade disconnects in a least-likely case.